Audit Lag, Tenure, Age, Size, Profitability and Solvent Resistance to Stock Volatility with Public Accountant Reputation as Moderation - Niken Savitri Primasari; Mohammad Ghofirin (Universitas Jember, 2021)
Accordance with the principle of transparancy of financial statements and annual reports announce by the public company as an important element to avoid the gap time that might causing potentially negative effects information for investors, which thus delayed information phenomenon of the annual report issuer's in year 2019 recorded still reaching 2.4 highest from the year 2018, while the largest increase delayed reporting in the year 2020 for financial performance year end 2019 occurs because of covid-19 pandemic. The research will be conducted on a group of manufacturing companies listed on the Indonesia Stock Exchange with period year 2015 until 2020 and not included in the delisting list until the year 2020. The results obtained audit report lag has significant effect on the stock volatility. Keywords: Audit Tenure, Lag, Age, Size, Profitability, Solvability, Stock Volatility